Rhetorical moves in problem statement section of Iranian EFL postgraduate students' theses - Nimehchisalem, Vahid; Tarvirdizadeh, Zahra; Sayed Paidary, Sara; Mat Hussin, Nur Izyan Syamimi (Australian International Academic Centre, 2016)
The Problem Statement (PS) section of a thesis, usually a subsection of the first chapter, is supposed to justify the objectives of the study. Postgraduate students are often ignorant of the rhetorical moves that they are expected to make in their PS. This descriptive study aimed to explore the rhetorical moves of the PS in Iranian master’s (MA) degree theses. The study focused on 30 PSs written by MA Teaching English as a Foreign Language (TEFL) students. The samples were analyzed based on Swales’ (1990) Create-a-research-space (CARS) model. The findings revealed the students’ flaws in writing the PS where they typically presented the significance of their study. The results of the analysis of their written samples also showed that some of the students failed to address a problem as an academic issue based on the existing gap in the previous studies and failed to recommend ways to solve the problem. Students’ awareness of the rhetorical structure of the PS may help them create higher-quality works in academic settings. This study has theoretical and pedagogical implications, a discussion of which concludes the paper.